Conflict-Free Path Planning for Autonomous Transport Vehicles - Yıldız, Özge Aslan; Yazıcı, Ahmet; Sarıçiçek, İnci (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Autonomous Transport Vehicles (ATVs) are flexible robotic systems for transportation tasks in intra-logistics. It is very important to determine the most cost-efficient routes for ATVs within factory environments. Conflicts occur if more than one ATV moves at the same point in the same time interval. Conflicts cause unwanted delays, and it is crucial to determine the conflict-free routes for ATVs on the shop floor. Efficiently planning conflict-free paths for multiple AGVs and minimizing overall task completion time are essential for assessing system performance. In the study, a NonConflict-A* (NC-A*) algorithm that is based on the A* algorithm has been proposed to solve conflict problems in multiple ATVs. Unlike studies in the literature, the proposed algorithm performs pathfinding, conflict detection, and conflict resolution simultaneously. The NC-A* algorithm detects the conflicts while obtaining the paths, chooses the conflict resolution strategy that is the least costly according to the conflict types and produces the most cost-efficient route. The proposed algorithm aims to minimize the total route duration time while ensuring system safety by detecting and resolving all potential conflicts. The algorithm is tested for different conflict types of multiple ATVs traveling at various speeds. The solutions of the algorithm show that the algorithm determines all of the conflicts, selects the appropriate solution strategy and generates conflict-free routes.